Uppskattning av stjärnbildningstakt hos galaxer i det unga universum - Tengnäs, Viktor; Lan, Richard; Perme, Andreas; Hallqvist, Filippa (My University, 2015)
Galaxies in the local universe are almost as old as the universe itself, many of the stars in these galaxies were formed billions of years ago. To get a more complete understanding of the formation and evolution of galaxies, we also need to study younger galaxies in distant regions. This bachelor's thesis uses existing methods in order to study distant galaxies from the time around 3 billion years after the Big Bang, when the star formation rate density is measured to have been at its highest. The aim is to determine the star formation rate and stellar mass of a sample of star-forming galaxies. We study a selection of galaxies of the type sBzK, which are star-forming galaxies at z 1:5 2:5. Interstellar dust is present in these star-forming galaxies, and the dust grains are heated by ultra-violet and optical light from young stars. The dust then re-emits the energy at far-infrared and submillimeter wavelengths. This thermal dust emission can therefore be used to estimate the star formation rate for these galaxies. Data, collected at submillimeter wavelengths, by the interferometric observatory ALMA is analysed and processed to extract the aforementioned properties of the sBzK galaxies. This sample of galaxies are generally too faint to be individually detected at millimeter wavelengths. Therefore two types of stacking methods, image and uv-stacking, are used to estimate their average properties. The results from the different stacking methods are compared with each other. Monte Carlo stacking with both methods is also performed in order to evaluate the results from the stacking processes. With the stacked ALMA data we were able to detect the sBzK sample. The obtained results using uv-stacking was a SFR of 212:3M=yr, when assuming = 1:6, T = 30K and a Chabrier initial mass function. Using image stacking we derive a similar star formation rate of 18 2:4M=yr. Based on simple assumptions we obtain an estimate for the stellar mass of 4;6 1010M. It is also found that the image stacked result gives a lower ux than the uv-stacked result, leading to higher star formation rates for the uv-stacked sources. This star formation rate can be compared to our current knowledge of our own galaxy.
Keywords: Data- och informationsvetenskap; Geovetenskap och miljövetenskap; Informations- och kommunikationsteknik; Materialvetenskap; Computer and Information Science; Earth and Related Environmental Sciences; Information & Communication Technology; Materials Science